2020
DOI: 10.1021/acs.jproteome.9b00825
|View full text |Cite
|
Sign up to set email alerts
|

Bait Correlation Improves Interactor Identification by Tandem Mass Tag-Affinity Purification-Mass Spectrometry

Abstract: The quantitative multiplexing capacity of isobaric Tandem Mass Tags (TMT) has increased the throughput of affinity purification mass spectrometry (AP-MS) to characterize protein interaction networks of immunoprecipitated bait proteins. However, variable bait levels between replicates can convolute interactor identification. We compared the Student's t-test and Pearson's R correlation as methods to generate t-statistics and assessed the significance of interactors following TMT-AP-MS. Using a simple linear mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Tryptic digests of the eluate were isobarically labeled with TMT tags, quantified by MuDPIT LC-MS, and relative protein abundances inferred from TMT reporter ion ratios for identified peptides. Interaction significance was determined using our previously reported bait correlation method 21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tryptic digests of the eluate were isobarically labeled with TMT tags, quantified by MuDPIT LC-MS, and relative protein abundances inferred from TMT reporter ion ratios for identified peptides. Interaction significance was determined using our previously reported bait correlation method 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Co-immunoprecipitated proteins are quantified by mass spectrometry using isobaric TMT labeling. We found that proteins that co-immunoprecipitate with Flag DNAJB8 H31Q are generally destabilized compared to the bulk proteome 21 . We used this Hsp40 affinity assay to identify proteins that are destabilized by brief cellular arsenite exposure, finding a series of known arsenite targets, and validated their destabilization by limited proteolysis.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…[18][19][20][21] We previously used affinity purification and quantitative proteomics to identify hundreds of cellular protein clients of overexpressed human Hsp40 DNAJB8 H31Q with high reproducibility and statistical confidence. [22] Herein we exploit the ability of DNAJB8 H31Q to recognize misfolded protein clients to develop a platform for identifying proteins that are destabilized in response to exogenous stress (Figure 1). We demonstrate this approach in HEK293T cells treated with trivalent arsenic, a toxic metal that causes widespread damage to nucleic acids and proteins, leading to genomic and metabolic instability.…”
mentioning
confidence: 99%